What Motivates People With (Pre)Diabetes to Move? Testing Self-Determination Theory in Rural Uganda - De Man, Jeroen; Wouters, Edwin; Absetz, Pilvikki; Daivadanam, Meena; Naggayi, Gloria; Kasujja, Francis Xavier; Remmen, Roy; Guwatudde, David; Olmen, Josefien Van (Frontiers in Psychology, 2020)
Sub-Saharan Africa is experiencing a rapid growth of type 2 diabetes (T2D) and its related burden. Regular physical activity (PA) is a successful prevention strategy but is challenging to maintain. Self-determination theory (SDT) posits that more autonomous forms of motivation are associated with more sustainable behavior change. Evidence to support this claim is lacking in sub-Saharan Africa. This study aims to explore the relationships between latent constructs of autonomous and controlled motivation, perceived competence, perceived relatedness, PA behavior, and glycemic biomarkers. Methods: Structural equation modeling was applied to cross-sectional data from a rural Ugandan population (N = 712, pre-diabetes = 329, diabetes = 383). Outcome measures included self-reported moderate and vigorous PA, pedometer counts, and fasting plasma glucose (FPG) and glycated hemoglobin (HbA1C). Results: Our findings support SDT, but also suggest that different types of motivation regulate different domains and intensities of PA. Higher frequency of vigorous PA – which was linked to a lower HbA1C and FPG – was predicted by autonomous motivation (β = 0.24) but not by controlled motivation (β = −0.05). However, we found no association with moderate PA frequency nor with pedometer counts. Perceived competence and perceived relatedness predicted autonomous motivation. Autonomous motivation functioned as a mediator between those needs and PA behavior. Conclusion: This is the first study providing evidence for a SDT model explaining PA among people at risk of, or living with, T2D in a rural sub-Saharan African setting. Our findings suggest that individuals who experience genuine support from friends or family and who feel competent in doing vigorous PA can become motivated through identification of health benefits of PA as their own goals. This type of motivation resulted in a higher frequency of vigorous PA and better glycemic biomarkers. On the other hand, people who felt more motivated through pressure from others or through feelings of guilt or shame were not more engaged in PA.
Keywords: Type 2 diabetes; Physical activity; Self-determination theory; Sub-saharan Africa; Uganda; Psychological needs theory; Autonomous motivation; Controlled motivation